Effect of copper ions on the associations of Azospirillum bacteria with wheat seedlings (Triticum aestivum L.) - A. Yu. Muratova; E. V. Lyubun; S. N. Golubev; O. V. Turkovskaya (Вавиловский журнал генетики и селекции)
The physiological and biochemical activity of plant–microbial associations enables them to determine the mobility, bioavailability, and accumulation of heavy metals in plant tissues. These abilities are the basis for the use of plants and their associated microorganisms in the development of approaches that ensure both the prevention of the ingress of toxic metals into food crops and the extraction of pollutants from polluted soils by using phytoremediation technologies. Whether plant–microbial complexes are used successfully depends on the knowledge of how specific organisms interact with heavy metals. We evaluated the effect of copper ions on common wheat (Triticum aestivum L.) inoculated with three plant-growth-promoting rhizobacteria (PGPR) of the genus Azospirillum. We analyzed the growth variables of 14-day-old wheat seedlings, the content of photosynthesis pigments, the activity of plant oxidoreductases, and the accumulation of copper by plant tissues. All strains more or less compensated for copper toxicity to seedling development and increased metal accumulation in roots and shoots. Copper affected the photosynthetic apparatus of the inoculated plants, primarily by decreasing the content of chlorophyll b. An analysis of the activity of plant oxidoreductases (peroxidases and phenoloxidases), which are involved in the physiological responses of plants to pollutant stress, showed strain-specific dependence and a significant effect of copper on the inoculated plants. Overall, the obtained results clearly show that the effect of Azospirillum on the physiological and biochemical status of wheat is diverse. The compensatory effect of bacteria on copper toxicity and the simultaneous increase in metal accumulation in plant tissues can be considered as mutually exclusive crop-production aspects associated with the growing of food plants in heavy-metal-polluted areas.